1996
DOI: 10.1159/000121047
|View full text |Cite
|
Sign up to set email alerts
|

Diffuse Brainstem Tumors: When is a Biopsy Necessary?

Abstract: This study addresses the role of biopsies in diffuse pediatric brainstem tumors. Biopsies have been advocated to confirm the diagnosis, to determine the tumor histology, to obtain prognostic information and because they can be done with low risk. Biopsies are opposed because diffuse brainstem tumors are gliomas, the histology does not correlate with prognosis nor with histology at autopsy, clinical and magnetic resonance scans provide prognostic information, biopsies have risks, and the biopsy does not alter t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
35
0
2

Year Published

1998
1998
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(42 citation statements)
references
References 18 publications
5
35
0
2
Order By: Relevance
“…In the present study, the success rate for the procedure was 93.7%, which is in agreement with previously published data showing that this rate varies from 87 to 100% [5,6,[10][11][12][13] . Furthermore, the present study verified a higher rate of diagnosis in patients submitted to the transfrontal approach than in those submitted to the suboccipital approach (95.1 vs. 84.2%); however, the difference observed was not statistically significant.…”
Section: Discussionsupporting
confidence: 93%
“…In the present study, the success rate for the procedure was 93.7%, which is in agreement with previously published data showing that this rate varies from 87 to 100% [5,6,[10][11][12][13] . Furthermore, the present study verified a higher rate of diagnosis in patients submitted to the transfrontal approach than in those submitted to the suboccipital approach (95.1 vs. 84.2%); however, the difference observed was not statistically significant.…”
Section: Discussionsupporting
confidence: 93%
“…Most authors regard biopsy procedures for intrinsic brainstem tumors as being too dangerous and consider imaging methods as sufficiently reliable. 1,5 Thus, the impact of MRI findings on treatment decisions for brainstem tumors is very high, but the accuracy of MRI-based diagnosis of diffuse brainstem gliomas has not been fully verified by histopathological findings. 8 Thus, some authors have reported that all diffuse brainstem gliomas located above the medulla behave as high-grade astrocytomas, and histological grade is not a significant factor for the survival of these patients.…”
Section: Discussionmentioning
confidence: 99%
“…8 Thus, some authors have reported that all diffuse brainstem gliomas located above the medulla behave as high-grade astrocytomas, and histological grade is not a significant factor for the survival of these patients. 1,4,5,18,20 Few studies have been conducted concerning prognosis and prognostic factors in brainstem gliomas. 1 This may be due to the low incidence of these tumors and the fact that histopathological diagnosis is rarely confirmed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As stated previously, these gliomas are typically malignant fibrillary astrocytomas which infiltrate along the white matter tracts into the midbrain and thalamus. They invariably have a rapidly progressive and dismal course, similar to the clinical course for glioblastoma multiforme in the brain [3, 55]. There is no role for radical surgery or biopsy since the tumor histology does not change the treatment strategy [56].…”
Section: Future Directionsmentioning
confidence: 99%